Impact of Mild Hypothermia on the Recovery of Patients with Acute Stroke - Abbas Rozbahani (پزشکی بالینی ابن سینا, 2019)
Background and Objective: Hypothermia induction has been proposed to improve the recovery process of stroke in the last two decades. Therefore, the aim of this study was to investigate the effect of mild hypothermia on the recovery of patients with acute stroke. Materials and Methods: This single-blind randomized clinical trial was conducted on 60 patients with acute stroke in 2018 in Hamadan, Iran. The patients were selected by available sampling method, and then randomly assigned into two equal-sized groups of intervention and control. Mild hypothermia was induced using a cooling device applied on the patientschr('39') head for a period of 72 h. The National Institutes of Health Stroke Scale (NIHSS) was used to collect the data. The results of both groups were compared with each other following the intervention. Finally, the data were analyzed using SPSS software (version 22). Results: The results showed no significant difference between the mean scores obtained before and after the intervention in the control group (P>0.05). In addition, there was no significant difference between the intervention and control groups in terms of the pre-intervention mean scores (P>0.05). However, the results revealed a statistically significant difference in the mean pre- and post-intervention scores of the intervention group (P<0.05). In this regard, the mean score of NIHSS was significantly reduced in the intervention group after the induction of hypothermia. Finally, the results were indicative of a statistically significant difference between the intervention and control groups after the intervention (P<0.05). Conclusion: As the findings of the present study indicated, noninvasively induced hypothermia has a significant clinical effect on acute stroke. Therefore, it can be argued that the use of hypothermia leads to the enhancement of consciousness level and reduction of mortality risk in patients with acute stroke. Consequently, this intervention is suggested to be considered the main therapeutic approach of acute stroke.